The winds of change : Buddhism and the maritime links of early South Asia - Ray, Himanshu Prabha (Delhi : Oxford University Press, 1994)
On maritime trade and seafaring in the early historical period with reference to support provided by Buddhist monastic establishments during that period.
Includes bibliographical references (p. [203]-222) and index.
Donated By Akbar Ali Khan
Keywords: Buddhism -- History -- To ca. 100 A.D.; Navigation -- India -- History; India -- Commerce -- History; India Ocean Region -- Commerce -- History; Southeast Asia -- Commerce -- India -- History